Deterministic Finite State Automatic Smartphone Sales at Handphone Store Using Vending Machine - Fikri Ismaya; Oky Kurniawan; Hafifah Bella Novitasari; Jordy Lasmana Putra; Windu Gata (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Mobile phones are getting more sophisticated from year to year, and there are many features that have the latest in these cellphones. Mobile phones have the fastest network today with fourth generation technology so it's not slow to watch videos, play games, study online, and so on. Mobile phones sold have variations of Android and Iphone Operating System. The sale of the cellphones is through mall counters, roadside counters, and street vendor counters. Cellphone sales counters still use tables, cell phone holders, brochures to promote cellphones, and others seem boring, there must be something unique to attract customers' attention. This study aims to develop innovation in selling cellphones that are unique and different from other cellphone stores. The research method uses Deterministic Finite State Automata on the Vending Machine. State Diagram design to define features, main view design, and purchase flow. The results of the study using Deterministic Finite State Automata in the Vending Machine design make it easier for buyers to make purchases of cellphones independently and have their own uniqueness to attract customers' attention